Prevalence of unlicensed medical practice in China: a retrospective analysis. (October 2016) - Xu, Beibei; Hu, Ya-Nan; Zhang, Qi; Wang, Hun; Wang, Zhao; Yu, Lu-Yu; Cao, Li-Ping; Yu, Guo-Pei; Hu, Yonghua
Abstract: Background: Unlicensed medical practice has been subject to high health supervision and inspection in China over the past decade. Unlicensed medical practice in China reflects not only the large gap between increases in demand and deficiencies in healthcare resources, but also the history and cultural background of the population. Our objectives were to describe current status of unlicensed medical practice and to discuss underlying causes of this phenomenon in China. Methods: Data on unlicensed medical practice from January 1, 2012, to December 31, 2015, collected by Center of Inspection and Supervision of National Health and Family Planning Commission through National Health Inspection Information System (NHIIS), were used to assess characteristics of cases of unlicensed medical practice in China. Data analyses were done using SAS (version 9·4). The underlying causes of unlicensed medical practice were also studied using government documents, academic papers, and media reports. Findings: Since 2005, unlicensed medical practice has become a national priority. Multiple Government Ministries collaborated with the aim of rectifying and standardising medical services, established long-term inspection mechanisms, and achieved initial results. Each province, autonomous region, and municipality has tried to restrict unlicensed medical practice following national plans and regulations as well as their own situation-specific procedures. 15 197 cases of unlicensed medical practice were reported in 2015—an increase of 2·0% since 2014 (14 893 cases), 17·8% since 2013 (12 494), and 41·4% since 2012 (8 911). Of all cases in 2015, 96% (14589 cases) were found with a permanent site, while the remaining cases worked from a mobile site. In 2015, 77% (11702 cases) of cases were imposed a penalty for the first time, 20% (3039 cases) were penalised at least once, and 3% (456 cases) were penalised twice or more. Interpretation: With strict enforcement, more cases of unlicensed medical practice have been detected and punished. However, causes of unlicensed medical practice in China are complex. To help policy makers reduce the risks associated with unlicensed medical practice, increased understanding the underlying reasons for unlicensed medical practice is needed. Funding: None.